New Zealand: Success for world's first indigenous organic verification system - Paull, John (2013)
The development of a Maori organic certification system, Hua Parakore, is reported in the latest New Zealand Organic Market Report. According to Brendan Hoare, chairperson of Organics Aotearoa New Zealand (OANZ), "The world's first indigenous organic verification system, Te Hua Parakore … is now setting a world benchmark for production by first nations people according to traditional values". The Report states that: "Hua Parakore is an indigenous verification and validation system for mahina kai (food and food production) that is initiated and driven by Te Waka Kai Ora, (National Maori Organics Authority of Aotearoa). It is the realisation of a community driven … Maori research project". The project is "Gaining momentum, with communities and businesses who are increasingly aware and committed to a system, which transforms and supports a pathway for growers and producers to tell their kaupapa Maori production story. It is also a development opportunity in the form of indigenous food sovereignty". The report states that "A key distinguishing feature of Hua Parakore is that it is informed by locally owned and managed indigenous systems that encourage cultural practice". The Hua Parakore project already has already some success with one produced reporting that: “since obtaining the Hua Parakore certification we have used the mark on our BioFarm yoghurt products whilst in Australia recently; in fact, we obtained distribution in the Australian market on the strength of our Maori organic certification”. The Maori organic certification project was launched in 2011 and is compliant with the New Zealand Standard for Organic Production. Under the Hua Parakore project there is already "a pilot farm", an apiary, "pastoral farming", and an interesting development is that of "one Hawaiian farm visiting and signing up to come under the Hua Parakore framework".